2016
DOI: 10.18632/oncotarget.6817
|View full text |Cite
|
Sign up to set email alerts
|

HBx regulates fatty acid oxidation to promote hepatocellular carcinoma survival during metabolic stress

Abstract: Due to a high rate of nutrient consumption and inadequate vascularization, hepatocellular carcinoma (HCC) cells constantly undergo metabolic stress during tumor development. Hepatitis B virus (HBV) X protein (HBx) has been implicated in the pathogenesis of HBV-induced HCC. In this study, we investigated the functional roles of HBx in HCC adaptation to metabolic stress. Up-regulation of HBx increased the intracellular ATP and NADPH generation, and induced the resistance to glucose deprivation, whereas depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 53 publications
(55 reference statements)
1
61
0
Order By: Relevance
“…These results confirm our previous hypothesis that more malignant tumors are usually characterized by a more modular expression pattern of cancer-associated genes [8,9]. We predict that higher modularity increases the fitness of tumors because metabolic networks are typically under increased stress in HCC tumor cells [34].…”
Section: One Interesting Phenomena Is a Non-monotonic Relation Betweesupporting
confidence: 91%
“…These results confirm our previous hypothesis that more malignant tumors are usually characterized by a more modular expression pattern of cancer-associated genes [8,9]. We predict that higher modularity increases the fitness of tumors because metabolic networks are typically under increased stress in HCC tumor cells [34].…”
Section: One Interesting Phenomena Is a Non-monotonic Relation Betweesupporting
confidence: 91%
“…In addition, cancer cells have their own ways to adapt to metabolic deprivation. [6][7][8] One study reported that nutrient deprivation can induce the Warburg effect, thereby indicating the role of the Warburg effect in helping cancer cells to overcome metabolic stress. 9 Otto Warburg first discovered that even with normal concentrations of oxygen, cancer cells prefer anaerobic breakdown of glucose over mitochondrial oxidative phosphorylation to generate energy, and this phenomenon is known as the "Warburg effect".…”
Section: Introductionmentioning
confidence: 99%
“…In response to viral infections, glycolysis may be increased or decreased, with beneficial results for viruses, for example, in the case of herpes simplex virus 1 and adenovirus infections (Abrantes et al, 2012;Thai et al, 2014). Studies found that HBV infection modulated host liver metabolic pathways, resulting in upregulation of glucose metabolism (e.g., gluconeogenesis, aerobic oxidation of glucose, and pentose phosphate pathway; Liu et al, 2015;Shin et al, 2011) and lipid metabolism (e.g., fatty acids, phospholipids, and cholesterol biosynthesis; Chen, Liang, Ou, Goldstein, & Brown, 2004;M. D. Wang et al, 2016;Yang et al, 2008).…”
mentioning
confidence: 99%